2019
DOI: 10.1111/1468-0009.12427
|View full text |Cite
|
Sign up to set email alerts
|

Issues Relevant to Population Health in Political Advertising in the United States, 2011‐2012 and 2015‐2016

Abstract: Political advertising can influence which issues are public policy priorities. Population health–relevant issues were frequently referenced in televised political advertising in the 2011‐2012 and 2015‐2016 US election cycles, with about one‐fourth of all ads aired mentioning traditional public health and health policy topics and more than half referencing broader determinants of population health. The volume of population health–relevant issues referenced in political ads varied by geography, political office,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Taking a more expansive and "upstream" conceptualization of the determinants of population health that encompassed issues like socioeconomic status, power, and marginalization, education, housing, and economic inequality (Braveman et al, 2011), the analysis revealed that 57% of all ads aired referenced at least one population health-related topic, including the traditional public health topics. While campaigns rarely connected the upstream set of issues to health explicitly (Fowler et al, 2019), the prevalence of references to these issues signals their importance to the public and conveys politicians' potential interest in addressing these issues through federal, state, and/or local policymaking.…”
Section: Campaign Ads and Population Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Taking a more expansive and "upstream" conceptualization of the determinants of population health that encompassed issues like socioeconomic status, power, and marginalization, education, housing, and economic inequality (Braveman et al, 2011), the analysis revealed that 57% of all ads aired referenced at least one population health-related topic, including the traditional public health topics. While campaigns rarely connected the upstream set of issues to health explicitly (Fowler et al, 2019), the prevalence of references to these issues signals their importance to the public and conveys politicians' potential interest in addressing these issues through federal, state, and/or local policymaking.…”
Section: Campaign Ads and Population Healthmentioning
confidence: 99%
“…The prevalence and frequency of references to population health-related topics varied widely across different geographic locations in the United States (Fowler et al, 2019). This variation in political messaging about population health-related topics could reflect actual differences in the underlying social conditions in communities, with more attention to poverty, for example, in areas with higher poverty.…”
Section: Campaign Ads and Population Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…We observe changes in health insurance advertising by varied sponsors and enrollment over time at the county level, identifying which types of advertising are associated with enrollment. We also assess the extent to which health-care-related political advertising plays a role, given that perceptions can be shaped by politicians responding to local preferences (Fowler, Baum, Jesch, et al 2019;Fording and Patton 2020;Pacheco, Haselswerdt, and Michener 2020), distinguishing between likely pro-ACA (pro-Democrat) and anti-ACA (pro-Republican) messages. Our study relies on a panel of counties and applies county fixed effects, exploiting variation in advertising and health insurance market environment within counties over time to assess the association of advertising with Marketplace enrollment.…”
Section: Rese a Rch Ob Jec Ti V Ementioning
confidence: 99%